Pengaruh Model Pembelajaran Kooperatif Tipe Pair Checks terhadap Hasil Belajar Fisika Siswa - Helliana; Wahyuni, Agus; Rizal, Syamsul (Journal of Technology and Literacy in Education, 2022)
This research aimed to find out is there significant difference between cooperative learning style by using pair checks method and convensional learning to physic s outcomes at grade X students’ in SMAN 2 Banda Aceh. The approach that is used in this research is quantitative approach by using experimental research. The design of this research in non-equivalent control grup design. The population in this research are all grade X students in SMAN 2 Banda Aceh. The sample in this research consist of 2 classes with the number of the students is 32 for experimental class and 31 students for controlling class. Purposive sampling is the sampling technique that is used in this research. The data collection is done by using testing and hypothesis technique with statistic one side t-test which is right side. The data analysis is at the significant level α = 5% and df = 61 showed that the value of tcount > ttable is 4,07 > 1,671. Based on the criteria of the test if tcount > ttable then Ha is accepted. Thus, it can be concluded that there is the significant difference between cooperative learning style by using pair checks method and convensional learning to physic s outcomes at grade X students’ in SMAN 2 Banda Aceh.